Portrayal of the Scottish Working Class in Alasdair Gray's Lanark - Zamastilová, Hana (Univerzita Pardubice, 2019)
The main purpose of this bachelor thesis is a literary analysis of Alasdair Gray's novel, Lanark. Firstly, topics such as identity, class-ridden society, Margaret Thatcher's policies are explained. There is also a description of the city of Glasgow. Afterwards, these topics are applied to the novel itself.
Vyobrazení skotské dělnické třídy v díle Alasdaira Graye, Lanark
Keywords: identity; working class; Thatcherism; Glasgow; Lanark; identita; dělnická třída; thatcherismus; Glasgow; Lanark